2004
DOI: 10.1007/s11106-005-0032-3
|View full text |Cite
|
Sign up to set email alerts
|

Ordering in the carbide W2C and phase equilibria in the tungsten ? carbon system in the region of its existence

Abstract: We have studied alloys in the W − C system with compositions 24 to 48 at.% C, melted in an arc furnace, homogenized and quenched from temperatures of 1450°C to 2650°C or cooled stepwise from a subsolidus temperature down to 850°C, and annealed for a prolonged period at this temperature or at temperatures close to it. We studied the specimens by x-ray single-crystal and powder diffraction, metallography, and differential thermal analysis. We have shown that the carbide W 2 C exists in two modifications: an hexa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 11 publications
1
15
0
Order By: Relevance
“…8,19,20,22, and 24͒ is given in Table I. Samples of W 2 C prepared by arc melting of W and WC mixtures with subsequent annealing at 1720-2120 K for 1.5 h and quenching to room temperature were studied 26,27 by the x-ray method. The structure was determined in W 2 C single crystals 0.2-0.5 mm in size taken from quenched samples.…”
Section: Crystal Structure Of Phases Of the Lower Tungsten Carbidmentioning
confidence: 99%
See 2 more Smart Citations
“…8,19,20,22, and 24͒ is given in Table I. Samples of W 2 C prepared by arc melting of W and WC mixtures with subsequent annealing at 1720-2120 K for 1.5 h and quenching to room temperature were studied 26,27 by the x-ray method. The structure was determined in W 2 C single crystals 0.2-0.5 mm in size taken from quenched samples.…”
Section: Crystal Structure Of Phases Of the Lower Tungsten Carbidmentioning
confidence: 99%
“…The structure was determined in W 2 C single crystals 0.2-0.5 mm in size taken from quenched samples. Velikanava and co-workers 26,27 found that at a temperature of ϳ2120 K, the disordered lower carbide ␤-W 2 C transforms to the trigonal ordered phase -W 2 C. According to Ref. 27, the trigonal phase -W 2 C is thermodynamically stable at temperatures of 2120-1520 K.…”
Section: Crystal Structure Of Phases Of the Lower Tungsten Carbidmentioning
confidence: 99%
See 1 more Smart Citation
“…The peculiarities of the phase formation in a W-C system as a function of W/C content and temperature were studied by means of systematic X-ray, dilatometric and microstructural experiments, and six different individual W-C phases were established. Among them, there are two mono-carbides WC-hexagonal (h) and cubic (c) and four phases (a, b, g and e) of semi-carbide W 2 C, see reviews in [8,17,18]. Some theoretical efforts have been made to understand the electronic structure and the origin of properties of these materials such as hardness, bulk modules and stability.…”
Section: Introductionmentioning
confidence: 99%
“…Cobalt exists in two modifications: a-Co (hexagonal, space group P63/mmc) and b-Co (cubic, space group Fm-3m) [22,23]. In WC-Co alloys, the transformation of WC carbide to W 2 C, Me 6 C, and Me 12 C carbides occurs due to decreasing carbon quantity in the alloy [24,25]. In the course of obtaining WC-Co alloys, the formation of the face-centered cubic (fcc) b-Co-based supersaturated solid solution which contains a large amount of W and C is possible [20,26].…”
Section: Introductionmentioning
confidence: 99%